Significance of Wireless Multi-Hop AD-HOC Networks - Pillai, Pradeep G; Saravanan, P (International Journal of Computer Sciences and Engineering, 2018)
The multi-hop ad hoc networking is not a new concept having been around for over twenty years, mainly exploited to design tactical networks. In the past decade wireless multi-hop ad-hoc networks have got a tremendous amount of research focus. Mobile devices enabled with wireless short range communication technologies make possible new applications for continuous communication, interaction and collaboration. The collaboration is used to facilitate communication when mobile devices are not able to establish direct communication paths. So the communication is multi-hop with intermediate nodes acting as routers that forward the messages addressed to other nodes. The multi-hop ad-hoc networking concept was successfully applied in several classes of networks. In this paper, it reviews the categories of wireless multi-hop ad-hoc networks and discusses main evolutions of wireless multi-hop ad-hoc networks specially the opportunistic networks. This networking paradigm is well suited for a world of pervasive devices equipped with various wireless networking technologies which are frequently out of range from a global network but are in the range of other networked devices, and sometime cross areas where some type of connectivity is available. Among multi-hop ad hoc networks, wireless sensor networks have a special role.